Characteristics of traditional Chinese medicine usage in patients with stroke in Taiwan: A nationwide population-based study. (20th June 2016) - Chang, Chia-Chi; Lee, Yu-Chen; Lin, Che-Chen; Chang, Chin-Hsien; Chiu, Cheng-Di; Chou, Li-Wei; Sun, Mao-Feng; Yen, Hung-Rong
Abstract: Ethnopharmacological relevance: Stroke has been the leading causes of death worldwide. Traditional Chinese medicine (TCM) has been used for stoke patients for thousands of years. This study aimed to investigate TCM usage and prescription patterns in stroke patients in Taiwan. Materials and methods: We analyzed a random sample of one million individuals representing the 23 million enrollees selected from the National Health Insurance Research Database in Taiwan. Demographic characteristics, TCM usage, prescription patterns and mortality rate among stroke patients were analyzed. Results: We identified 23, 816 patients who were newly diagnosed with stroke between 2001 and 2009 by their diagnostic codes (ICD-9-CM 430–438). Among them, 4302 patients had hemorrhagic stroke while 19, 514 patients had ischemic stroke. Overall, 12% of the stroke patients (n=2862) were TCM users. The median interval between stroke onset to the first TCM consultation is 12.2 months. Among the TCM users, more than half (52.7%) of the patients received both Chinese herbal remedies and acupuncture/traumatology treatment. Bu-yang-huan-wu-tang and Dan-shen ( Radix Salviae Miltiorrhizae; Salvia miltiorrhiza Bunge) was the most commonly prescribed Chinese herbal formula and single herb, respectively. TCM users had a higher incidence rate ratio in myalgia, myositis, fasciitis and insomnia than non-TCM users. Mental disorders such as anxiety and depression are common in both TCM and non-TCM users. Comparing with the non-TCM users, the TCM users had a lower mortality rate (adjusted hazard ratios were 0.44 in overall stroke, 0.50 in ischemic stroke and 0.25 in hemorrhagic stroke). Conclusion: Adjunctive TCM use may reduce the risk of mortality rate among stroke patients. Bu-yang-huan-wu-tang and Dan-shen are the most common prescribed Chinese herbal formula and single herb for stroke patients, respectively. Future study investigating the anti-inflammatory and neuroprotective efficacy of Bu-yang-huan-wu-tang and Dan-shen in stroke is warranted. Graphical abstract: